A reevaluation of Brachyprosopus broomi and Chelydontops altidentalis, dicynodonts (Therapsida, Anomodontia) from the middle Permian Tapinocephalus Assemblage Zone of the Karoo Basin, South Africa. Issue 2 (3rd March 2016) - Angielczyk, Kenneth D.; Rubidge, Bruce S.; Day, Michael O.; Lin, Florence
ABSTRACT: Brachyprosopus broomi was described in 1937 based on a specimen from the Tapinocephalus Assemblage Zone (Karoo Basin, South Africa), but it was largely overlooked by subsequent workers. We have identified several new specimens that show that Brachyprosopus is a valid taxon. An autapomorphy for the taxon is a curled lateral edge of the squamosal that forms a lateral wall of the external adductor fossa. Other important characters are absence of anterior median palatal ridges; maxillary tooth rows bounded laterally by a shelf; unfused vomers; raised margins of the interpterygoid vacuity; broad intertemporal region; pineal boss; dentary tables; and a long, wide posterior dentary sulcus that extends posterior to the dentary teeth. Chelydontops altidentalis is a junior synonym of B. broomi . A phylogenetic analysis places Brachyprosopus among basal dicynodonts, not as a close relative of Endothiodon . It is noteworthy that some characters, such as well-developed medial maxillary tooth rows and the shape of the palatines, are shared by Brachyprosopus, Pristerodon, Endothiodon, and Niassodon, hinting that a final resolution of relationships among toothed dicynodonts remains to be achieved. Most Brachyprosopus specimens are from the upper Abrahamskraal Formation (Moordenaars and Karelskraal members). One specimen is from low in the Koonap Formation, just above the lowermost maroon mudrocks of the Beaufort Group, and an exact correlation between this level and the strata of the Abrahamskraal Formation is uncertain. Therefore, it is likely that the stratigraphic range of Brachyprosopus extends throughout the Tapinocephalus zone and possibly down into the Eodicynodon Assemblage Zone. SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Angielczyk, K. D., B. S. Rubidge, M. O. Day, and F. Lin. 2016. A reevaluation of Brachyprosopus broomi and Chelydontops altidentalis, dicynodonts (Therapsida, Anomodontia) from the middle Permian Tapinocephalus Assemblage Zone of the Karoo Basin, South Africa. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2016.1078342.